Effect of Yellow and Stop Drosophila Normal Anti-insect Photoselective Nets on Vegetative, Generative and Bioactive Traits of Peach (cv. Suncrest) - Slaven Jurić; Marko Vinceković; Branka Levaj; Goran Fruk; Tomislav Jemrić; Marko Vuković (Journal of Agricultural Sciences)
The effect of anti-insect photoselective yellow (mesh size of 2.4x4.8 mm) and Stop Drosophila Normal (mesh size of 0.90x1 mm) nets on the generative and vegetative traits of peach (cv. Suncrest) was studied at an orchard near the city of Čakovec, Croatia. Netting significantly affected some vegetative parameters (leaf surface, leaf length and leaf shape index) but there was no significant effect on productivity parameters (yield, yield efficiency, fruit mass and share of decayed fruit). Regarding fruit colouration application of nets significantly affected b* and C* background and L*, b*, C* and h° additional colour parameters. Majority of inner fruit quality parameters (fruit firmness, titratable acidity and total soluble solids / titratable acidity ratio) as well as of bioactive compounds (total polyphenolic content, antioxidant activity, anthocyanin content and share of alkali-soluble pectin) was also under significant effect of netting. Since yellow net only slightly reduced peach fruit quality (compared to control) it can be recommended for application as an anti-insect net. However, Stop Drosophila Normal net more notably reduced quality parameters (especially additional fruit colour) and hence should be used only when other control strategies show to be ineffective.